Mental and physical conditions associated with physical inactivity among Farhangian University students during virtual classes: A cross-sectional study - Homayounnia Firouzjah, Morteza; Pourazar, Morteza; Kakvandi, Saeed Nazari (Frontiers in Psychology, 2023)
Background: The level of mobility and general health has decreased among students in virtual classes during covid-19 pandemic. The present cross-sectional study aims to investigate the mental and physical complications caused by inactivity among the students of Farhangian University during the virtual classes. Methods: This is a cross-sectional study. 475 students (214 females and 261 males) were selected as the statistical sample of the study based on Morgan's Table from Farhangian University, Iran. The statistical population includes students studying at Farhangian University of Mazandaran province that using Convenience Sampling the sample size based on Morgan's Table, 475 students consisting of 214 females and 261 males were randomly selected as the statistical sample of the study. The research instruments of this study include International Physical Activity Questionnaire, Saehan Caliper (SH5020), Coopersmith Self-Esteem Scale (1967), Beck Depression Questionnaire, and Nordic Skeletal and Muscular Disorders Questionnaire. For data analysis, independent sample t-test was employed to compare two groups. All analyses were conducted using spss24 software. Results: with respect to students’ skeletal-muscular disorders, findings proved that both genders suffered physical complications during virtual classes. The research findings showed that the average weekly activity level among women is 634 Met/min with a standard deviation of ±281, and the average weekly activity level among men is 472 Met/min with a standard deviation of ±231. Fat percentage by gender, men’s average fat percentage is 47.21% (S. D±4.74) and women’s average fat percentage is 31.55% (S. D±4.37). Also, the self-esteem scores of male and female students were obtained 29.72 and 29.43, respectively, and the difference between the two was considered significant (P<0.05). In addition to these findings, the correlation between self-esteem and activity level is +0.41. On the other hand, 67% (No. 25) of female students and 32% (No. 12) of male students suffered from high depression. Conclusion: This study suggests increasing the level of physical activity to reduce body fat mass, increase mental health and reduce skeletal disorders, which can be properly accomplished through university planning and prioritizing the health of male and female students.